Polarization phenomena in the process e⁺ + e⁻ ↔ N + Ň in presence of two-photon exchange - Gakh, G.I.; E., Tomasi-Gustafsson (Вопросы атомной науки и техники, 2007)
General properties of the differential cross section and of various polarization observables are derived for the e⁺ + e⁻ ↔ N + Ň reaction, in presence of two-photon exchange. Polarization effects are investigated for longitudi-nally polarized electron beam and polarized antinucleon and/or polarized nucleon in the final state. Отримані загальні властивості диференційного перерізу та різних поляризаційних спостережуваних для реакції e⁺ + e⁻ ↔ N + Ň при наявності двухфотонного обміну. Досліджені поляризаційні ефекти, коли початковий пучок електронів має повздовжню поляризацію, а в кінцевому стані поляризовані антинуклон і/або нуклон. Получены общие свойства дифференциального сечения и различных поляризационных наблюдаемых для реакции e⁺ + e⁻ ↔ N + Ň при наличии двухфотонного обмена. Исследованы поляризационные эффекты, когда начальный пучок электронов имеет продольную поляризацию, а в конечном состоянии поляризованы антинуклон и/или нуклон.